Regeneration method of retired lithium iron phosphate positive electrode material
By using pressurized CO2 heat treatment and lithium salt replenishment, the problem of removing carbon impurities in retired lithium iron phosphate cathode materials was solved, thereby improving the structural stability and electrochemical performance of the materials and enabling them to have high discharge capacity and good cycle performance.
Patent Information
- Application Number
- CN202511497959.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-20
- Publication Date
- 2026-01-13
AI Technical Summary
In the existing technology for repairing retired lithium iron phosphate cathode materials, it is difficult to effectively remove carbon impurities, resulting in poor material consistency and insufficient electrochemical performance. In particular, the lithium/iron antisite defect rate is high, the structure is unstable, and the cycle performance and rate performance are affected.
A pressurized CO2-assisted heat treatment method is adopted to selectively remove impurities such as binders and conductive carbon nanotubes through the disproportionation reaction of CO2 and carbon. At the same time, lithium salt is added under high pressure to repair structural defects, form a continuous conductive network, and promote lithium-ion intercalation.
A regenerated lithium iron phosphate material with low lithium/iron antisite defect rate has been achieved. It has good structural stability, high discharge capacity, good cycle performance and rate performance, and avoids the complexity and energy consumption problems of traditional multi-step regeneration process.
Smart Images

Figure CN121332013A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium-ion battery technology, and particularly relates to a method for regenerating retired lithium iron phosphate cathode materials. Background Technology
[0002] In recent years, with the rapid development of new energy vehicles and energy storage, lithium iron phosphate (LiFePO4, LFP) batteries have been widely used due to their high safety, long cycle life, and low cost. This has led to the problem of disposing of a large number of retired LFP batteries, making the recycling and regeneration of their cathode materials a key issue for resource recycling and environmental protection.
[0003] Currently, the recycling methods for retired LFP cathode materials mainly fall into two categories: hydrometallurgical recycling and direct remediation. Hydrometallurgy typically uses acid leaching to extract valuable metal elements (such as lithium, iron, and phosphorus), which are then further converted into products such as lithium carbonate and iron phosphate. While this method can achieve a high lithium recovery rate (>90%), it is complex, consumes large amounts of reagents, generates significant wastewater and waste residue, resulting in a heavy environmental burden and poor economic efficiency. In contrast, direct remediation, due to its shorter process, lower energy consumption, smaller chemical reagent usage, and lower carbon emissions, has become a more promising green recycling strategy. This method aims to restore the electrochemical performance of LFP without damaging its olivine structure through lithium replenishment, defect repair, and lattice reconstruction. Numerous studies have already explored this direction. In 2016, GEM Co., Ltd. first improved the separation of cathode materials and electrode sheets by using porous materials in its published patent CN106450558B (Separation and Repair Method of Cathode Material for Waste Lithium Iron Phosphate Batteries). The lithium iron phosphate cathode sheet was placed in an inert atmosphere, and microporous carbon microspheres or mesoporous carbon microspheres with pore sizes less than 20 nm and particle sizes less than 1 μm were added and calcined with lithium salt. During calcination, the aluminum foil in the material melts into liquid aluminum. Due to its strong pore adsorption force, the porous microspheres in the mixed material can effectively adsorb the liquid material, thereby separating the liquid aluminum from the solid cathode material. During the heating process, the added lithium salt undergoes a lithium replenishment and regeneration reaction with the retired lithium iron phosphate material. The repaired lithium iron phosphate material has a discharge specific capacity of 164 mAh / g in the first week, and after 20 cycles, its specific capacity remains at 163 mAh / g.
[0004] In 2019, Lithium Source (Shenzhen) Scientific Research Co., Ltd. proposed in its published patent CN113036253B (Method for Selective Oxidation-Reduction Regeneration of Waste Lithium Iron Phosphate, Regenerated Lithium Iron Phosphate and Lithium-ion Batteries) to sinter waste lithium iron phosphate using a mixture of steam and CO2. This selectively oxidizes and removes amorphous carbon while retaining graphitized carbon, avoiding the problem of aluminum foil corrosion caused by the inability to react with organic matter under inert atmosphere heat treatment. The repaired lithium iron phosphate material obtained by a second sintering after a first sintering in a mixture of steam and CO2 and supplementing lithium and carbon exhibits a capacity retention of ≥99% after 200 cycles at 1C, a capacity of 161.4 mAh / g at 0.1C, and 140.5 mAg / h at 1C.
[0005] In 2022, Zhuzhou Smelting Group Co., Ltd. proposed in its patent CN114566727A (a modification method for direct pyrometallurgical repair and regeneration of lithium iron phosphate cathode material) that lithium iron phosphate is obtained by adding lithium source, iron source, phosphorus source, aluminum source and activator after aerobic roasting, ball milling and spray drying, and then sintering. To achieve a more uniform solid-phase reaction and improve lithium replenishment efficiency, in 2022, Tsinghua University Shenzhen International Graduate School proposed a molten salt regeneration method for repairing and regenerating lithium iron phosphate in CN115000555A (A Direct Repair Method for Highly Defective Cathode Materials in Waste Lithium-ion Batteries). First, a binary eutectic lithium salt is prepared in a specific ratio. This eutectic lithium salt has a lower melting point than single-component lithium salts. Waste lithium iron phosphate is then mixed with the binary eutectic lithium salt and transition metal oxides, followed by a first-stage heat treatment at 200-500℃. At this point, the binary eutectic lithium salt melts into a liquid state, forming a homogeneous liquid reaction environment rich in lithium ions. A second-stage heat treatment at 600-900℃ further repairs and regenerates the waste lithium iron phosphate material, achieving a discharge specific capacity of 141 mAh / g at a current density of 0.5C.
[0006] While these methods effectively improve the performance of decommissioned lithium iron phosphate (LFP) materials, they are all affected by impurities during the repair process, resulting in poor consistency and insufficient electrochemical performance of the repaired LFP materials. Among various impurities, copper, aluminum, and iron can be controlled within the required range through pre-treatment such as fine disassembly and sorting, but effective methods for carbon removal are still lacking. There are two reasons why carbon is difficult to remove: first, the coated carbon is tightly bonded to the LFP material, and conductive agents such as carbon nanotubes adhere to the LFP material surface through binders, making physical separation difficult; second, while heating with air or oxygen can remove conductive agents such as acetylene black and carbon nanotubes, binders, and coated carbon, it also oxidizes the LFP material into ferric oxide (Fe2O3), a crystal transformation that further complicates the material repair process.
[0007] The presence of carbon poses several challenges to the remediation of decommissioned lithium-ion fuel (LFP) materials. First, remediation typically requires the addition of elements such as lithium, but the carbon coating hinders the migration of these elements into the material's interior, potentially leading to severe lithium / iron antisite defects, structural instability, and poor cycle performance. Second, excessive carbon in the remediated material consumes more electrolyte, increasing interfacial reactions and irreversible capacity, while also hindering lithium-ion diffusion during charge and discharge, resulting in insufficient rate performance. Therefore, developing carbon removal methods to ensure the stability and good electrochemical performance of remediated LFP materials is urgently needed. Summary of the Invention
[0008] To address the aforementioned technical problems, this invention proposes a method for regenerating retired lithium iron phosphate cathode materials. This method involves removing carbon impurities, especially inorganic carbon, through pressurized CO2-assisted heat treatment, while simultaneously repairing structural defects. Selective carbon removal exposes active sites, promoting lithium migration, while residual carbon maintains the conductive network. Furthermore, high voltage inhibits material agglomeration, ensuring structural uniformity. Therefore, compared to traditional methods, the regenerated lithium iron phosphate material exhibits a lower lithium / iron antisite defect rate and a more stable structure, while also ensuring stable composition and guaranteed electrochemical performance.
[0009] This invention proposes a method for regenerating retired lithium iron phosphate cathode materials, comprising the following steps: S1. Mix the retired lithium iron phosphate cathode material and lithium salt supplement in an organic solvent to obtain a precursor mixture; S2. The precursor mixture is subjected to a repair reaction under a high-pressure CO2 atmosphere to obtain recycled lithium iron phosphate material.
[0010] In this invention, retired lithium iron phosphate cathode material and lithium salt supplement are first mixed to form a precursor. Then, a repair reaction is carried out under a high-pressure CO2 atmosphere. On the one hand, impurities such as binders, conductive carbon nanotubes and some surface-coated carbon in the retired LFP material can be controlledly removed through the disproportionation reaction of carbon dioxide and carbon. On the other hand, the exposed LFP surface after carbon removal reduces the lithium migration resistance and promotes lithium ion insertion into the crystal lattice. Therefore, the lithium salt supplement can achieve lithium insertion repair in situ. Compared with direct calcination lithium insertion repair, the former can simultaneously repair crystal structure defects (such as Li / Fe antisite defects) caused by lithium loss, and obtain better repair effect.
[0011] Preferably, the retired lithium iron phosphate cathode material is obtained by discharging and disassembling retired lithium batteries, separating aluminum foil by dissolving the binder and electrolyte with N-methylpyrrolidone, and then drying the resulting slurry. Preferably, the discharge time is 24-48 hours; Preferably, the drying temperature is 70-80℃ and the drying time is 8-10h.
[0012] Preferably, in step S1, the lithium salt supplement is at least one of lithium carbonate, lithium hydroxide, lithium fluoride, lithium bromide, or lithium acetate; the organic solvent is a C1-C4 alcohol solvent, preferably ethanol. Preferably, the mass ratio of the decommissioned lithium iron phosphate cathode material to the lithium salt supplement is 100:0.5-5, and more preferably 100:2-3.
[0013] Preferably, step S1 further includes adding catechol-modified cyclodextrin; Preferably, the mass ratio of the decommissioned lithium iron phosphate cathode material to catechol-modified cyclodextrin is 100:0.5-5, and more preferably 100:1-3.
[0014] Preferably, the catechol-modified cyclodextrin is made by... β - The condensation of cyclodextrin with 1,3-propanediamine, followed by a Schiff base reaction with 3,4-dihydroxybenzaldehyde, yields the product. Preferably, the β- The mass ratio of cyclodextrin, propylene diamine, and 3,4-dihydroxybenzaldehyde is 10:20-50:1-3.
[0015] The structure of the catechol-modified cyclodextrin in this invention is shown below:
[0016] In this invention, the catechol-modified cyclodextrin has two advantages. First, based on the excellent inclusion and adsorption capabilities of the modified cyclodextrin, when it works together with lithium salt supplements, it can adsorb and fix lithium ions, ensuring that lithium ions can diffuse precisely on the LFP surface. Second, the multiple hydroxyl groups of catechol can repair the structural defects of waste lithium iron phosphate, creating a good reducing environment for it, further accelerating the transport of lithium ions and electrons, and enhancing the electrochemical stability of the recycled lithium iron phosphate material.
[0017] Preferably, in step S1, the mixing method is ball milling. Preferably, the ball-to-material mass ratio of the ball mill mixture is 5-20:1, more preferably 8-12:1, and the rotation speed is 200-500 rpm, more preferably 300-400 rpm.
[0018] Preferably, in step S2, the partial pressure of the CO2 atmosphere is 2-5 MPa, more preferably 3-3.5 MPa, and the purity of the atmosphere is ≥99.5 vol.
[0019] Preferably, in step S2, the temperature of the repair reaction is 500-800℃, more preferably 670-690℃, the heating rate is 3-10℃ / min, and the time is 4-6h, more preferably 4.5-5.5h.
[0020] This invention utilizes the synergistic effect of temperature, atmosphere, and pressure to remove inorganic carbon such as carbon nanotubes and partially coated carbon. The exposed surface of the decommissioned lithium iron phosphate material after carbon removal facilitates lithium intercalation. Because the exposed material surface after carbon removal reduces the migration resistance of supplemented lithium, the regenerated lithium iron phosphate material has a lower lithium / iron antisite defect rate and a more stable structure. At the same time, the removal of impurities such as carbon nanotubes ensures the stability of the composition of the regenerated lithium iron phosphate material, while the retained partially coated carbon provides a conductive network, ensuring electrochemical performance.
[0021] Preferably, the repair reaction further includes: cooling to room temperature; the cooling rate is 3-5°C / min.
[0022] The present invention also proposes a regenerated lithium iron phosphate material, which is prepared by the above-mentioned regeneration method.
[0023] The present invention also proposes a lithium-ion battery comprising the above-mentioned recycled lithium iron phosphate material.
[0024] The core inventive points of this invention are as follows: (1) Controllable carbon removal: Through the disproportionation reaction of CO2 and carbon (C+CO2→2CO), impurity carbon (such as binder and conductive carbon nanotubes) in decommissioned LFP materials is selectively removed under pressure ≥2MPa, while retaining part of the coated carbon layer.
[0025] (2) In-situ lithium insertion repair: After carbon removal, the exposed LFP surface reduces the lithium migration resistance, promotes lithium ion insertion into the lattice, and simultaneously repairs crystal structure defects caused by lithium loss (such as Li / Fe antisite defects).
[0026] (3) Pressure enhancement effect: The high-pressure CO2 environment increases the CO2 concentration around carbon, accelerates the neutralization reaction, and enhances the carbon removal effect; at the same time, high pressure can inhibit the high-temperature agglomeration of particles and maintain the uniform dispersion of materials; although increasing the temperature can promote the removal of carbon impurities, excessively high temperature will cause LFP particles to agglomerate; agglomeration increases the particle size, increases the path and resistance of lithium ion diffusion, and hinders lithium ion insertion, thus increasing the lithium / iron antisite defect rate.
[0027] (4) One-step integration: Carbon removal and lithium replenishment are integrated into a single high-temperature treatment step, avoiding the complexity and energy consumption problems of traditional multi-step regeneration processes.
[0028] (5) Precise control of carbon residue: Some coated carbon is retained to form a continuous conductive network, balancing surface activity and electronic conductivity. Carbon removal is beneficial for obtaining stable repaired LFPs. Appropriate removal of coated carbon can preserve the conductive network while exposing the surface. This not only ensures sufficient lithium replenishment during the repair process and reduces the lithium / iron antisite defect rate, but also allows the remaining coated carbon to provide a conductive network for the LFP material, ensuring good conductivity. Therefore, the repaired LFP material has high discharge capacity, good cycle performance, and rate performance.
[0029] This invention employs an innovative high-temperature pressurized CO2 atmosphere treatment strategy, which cleverly combines selective carbon removal with in-situ solid-state lithium replenishment: Under temperatures ≥500℃, a disproportionation reaction occurs between CO2 and carbon impurities (C + CO2 → 2CO). This reaction effectively removes residual electrolyte, binder, and other organic carbon, as well as some amorphous carbon, while retaining most of the graphitized carbon coating. The retained carbon coating forms a continuous three-dimensional electronic conductivity network, providing excellent electronic conductivity for the regenerated material, which is key to achieving superior rate performance. More importantly, during the carbon removal process, the exposed LFP particle surface reduces lithium migration resistance, promotes in-situ lithium ion insertion into the lattice, and simultaneously repairs crystal structure defects caused by lithium loss (such as Li / Fe antisite defects), thereby restoring the integrity and stability of the material's crystal structure. This in-situ repair mechanism effectively avoids the pollution and capacity loss that may result from multi-step processing, enabling the regenerated LFP material to exhibit high discharge capacity, good cycle performance, and rate performance. This invention also places particular emphasis on the regulation of pressure parameters. It has been found that increasing the partial pressure of CO2 can not only significantly accelerate the disproportionation reaction kinetics and enhance the carbon removal efficiency by increasing the reactant concentration, but also suppress the migration and agglomeration tendency of LFP particles at high temperatures. This helps to maintain the original particle size distribution and structural integrity of the material, creating favorable conditions for the efficient and uniform insertion of lithium ions and promoting lithium replenishment.
[0030] Compared with the prior art, the present invention has the following technical effects: (1) The method described in this invention adopts a one-step integrated in-situ repair method of “first replenishing lithium and then introducing CO2 oxidation sintering”, which can effectively avoid the pollution problems and capacity loss risks that may be introduced in the multi-step process, so that the regenerated lithium iron phosphate (LFP) material exhibits excellent electrochemical performance, and avoids the complexity and energy consumption problems of traditional multi-step regeneration process.
[0031] (2) The method described in this invention not only ensures sufficient lithium replenishment during the repair process and reduces the lithium / iron antisite defect rate, but also ensures good conductivity and structural stability of the recycled material. The repaired LFP material has high discharge capacity, good cycle performance and rate performance. Attached Figure Description
[0032] Figure 1 This is a flowchart of the regeneration method for retired lithium iron phosphate cathode materials according to the present invention; Figure 2 The charge-discharge curves of the recycled lithium iron phosphate material described in Example 1 of this invention at a current of 0.1C-1C are shown. Figure 3 The infrared spectrum of the catechol-modified cyclodextrin described in Example 4 of this invention is shown. Detailed Implementation
[0033] The technical solution of the present invention will be described in detail below through specific embodiments. However, it should be clearly stated that these embodiments are for illustrative purposes only and are not intended to limit the scope of the present invention.
[0034] Example 1 A method for regenerating retired lithium iron phosphate (LFP) cathode materials specifically includes the following steps: (1) After the retired LFP battery was discharged and disassembled for 24 hours, the aluminum foil was separated by soaking in N-methylpyrrolidone (NMP). The resulting LFP cathode slurry was vacuum dried at 75°C for 10 hours to obtain the retired LFP cathode material (elemental composition: Fe 33.6wt%, P 18.5wt%, Li 3.8wt%, C 4.2wt%). (2) Mix 100g of the retired LFP cathode material with 3g of lithium carbonate, add anhydrous ethanol, place in a ball mill jar at a ball-to-material mass ratio of 10:1, and ball mill at 400rpm for 4h. Dry the resulting slurry under vacuum at 80℃ for 12h to obtain a precursor mixture. (3) The precursor mixture was placed in a tube furnace and CO2 gas with a purity ≥99.8 vol% was introduced until the partial pressure reached 3.5 MPa. The mixture was heated to 680°C at a heating rate of 5°C / min and kept at the temperature for 5 hours for the repair reaction. After the reaction was completed, the temperature of the tube furnace was controlled to drop to room temperature at a cooling rate of 4°C / min to obtain the regenerated LFP cathode material. After grinding and passing through a 200-mesh sieve, the carbon content was measured to be 3.6 wt%.
[0035] Example 2 A method for regenerating retired lithium iron phosphate (LFP) cathode materials specifically includes the following steps: (1) After the retired LFP battery was discharged and disassembled for 24 hours, the aluminum foil was separated by soaking in N-methylpyrrolidone (NMP). The resulting LFP cathode slurry was vacuum dried at 75°C for 10 hours to obtain the retired LFP cathode material (elemental composition: Fe 33.6wt%, P 18.5wt%, Li 3.8wt%, C 4.2wt%). (2) Mix 100g of the retired LFP cathode material with 2g of lithium acetate, add anhydrous ethanol, place in a ball mill jar at a ball-to-material mass ratio of 20:1, and ball mill at 300rpm for 4h. Dry the resulting slurry under vacuum at 80℃ for 12h to obtain a precursor mixture. (3) The precursor mixture was placed in a tube furnace and CO2 gas with a purity ≥99.8 vol% was introduced until the partial pressure reached 2 MPa. The mixture was heated to 500°C at a heating rate of 3°C / min and kept at the temperature for 6 hours for the repair reaction. After the reaction was completed, the temperature of the tube furnace was controlled to drop to room temperature at a cooling rate of 5°C / min to obtain the regenerated LFP cathode material. After grinding and passing through a 200-mesh sieve, the carbon content was measured to be 3.8 wt%.
[0036] Example 3 A method for regenerating retired lithium iron phosphate (LFP) cathode materials specifically includes the following steps: (1) After the retired LFP battery was discharged and disassembled for 24 hours, the aluminum foil was separated by soaking in N-methylpyrrolidone (NMP). The resulting LFP cathode slurry was vacuum dried at 75°C for 10 hours to obtain the retired LFP cathode material (elemental composition: Fe 33.6wt%, P 18.5wt%, Li 3.8wt%, C 4.2wt%). (2) Mix 100g of the retired LFP cathode material with 3g of lithium hydroxide, add anhydrous ethanol, place in a ball mill jar at a ball-to-material mass ratio of 5:1, and ball mill at 400rpm for 4h. Dry the resulting slurry under vacuum at 80℃ for 12h to obtain a precursor mixture. (3) The precursor mixture was placed in a tube furnace and CO2 gas with a purity ≥99.8 vol% was introduced until the partial pressure reached 5 MPa. The mixture was heated to 800°C at a heating rate of 10°C / min and kept at the temperature for 4 hours for the repair reaction. After the reaction was completed, the temperature of the tube furnace was controlled to drop to room temperature at a cooling rate of 3°C / min to obtain the regenerated LFP cathode material. After grinding and passing through a 200-mesh sieve, the carbon content was measured to be 3.5 wt%.
[0037] Example 4 A method for regenerating retired lithium iron phosphate (LFP) cathode materials specifically includes the following steps: (1) After the retired LFP battery was discharged and disassembled for 24 hours, the aluminum foil was separated by soaking in N-methylpyrrolidone (NMP). The resulting LFP cathode slurry was vacuum dried at 75°C for 10 hours to obtain the retired LFP cathode material (elemental composition: Fe 33.6wt%, P 18.5wt%, Li 3.8wt%, C 4.2wt%). (2) Mix 100g of the retired LFP cathode material with 3g of lithium carbonate and 2g of catechol-modified cyclodextrin, add anhydrous ethanol, place in a ball mill jar at a ball-material mass ratio of 10:1, and ball mill at 400 rpm for 4 hours. Dry the resulting slurry under vacuum at 80°C for 12 hours to obtain a precursor mixture. The catechol-modified cyclodextrin is prepared by the following method: 10g β Cyclodextrin was dissolved in sodium hydroxide solution (2 wt%), and 3 g of p-toluenesulfonyl chloride was added under an ice-water bath. After stirring for 0.5 h, hydrochloric acid was added to adjust the pH to 8, and the reaction was stirred for 1 h. The mixture was then filtered, washed with water, and dried. The resulting intermediate was added to 1,3-propanediamine and reacted at 80 °C for 4 h. After cooling, the precipitate was poured into ethanol, filtered, washed with alcohol, and dried to obtain propanediamine-modified β-cyclodextrin. The obtained propanediamine-modified β-cyclodextrin was added to N,N-dimethylformamide (DMF), and a DMF solution containing 2 g of 3,4-dihydroxybenzaldehyde was added. The mixture was stirred at 60 °C for 3 h, cooled, and then poured into ethanol to precipitate. The precipitate was then filtered, washed with alcohol, and dried to obtain the catechol-modified cyclodextrin. Its infrared spectrum is shown in the figure. Figure 3 As shown; (3) The precursor mixture was placed in a tube furnace and CO2 gas with a purity ≥99.8 vol% was introduced until the partial pressure reached 3.5 MPa. The mixture was heated to 680°C at a heating rate of 5°C / min and kept at the temperature for 5 hours for the repair reaction. After the reaction was completed, the temperature of the tube furnace was controlled to drop to room temperature at a cooling rate of 4°C / min to obtain the regenerated LFP cathode material. After grinding and passing through a 200-mesh sieve, the carbon content was measured to be 3.7 wt%.
[0038] Comparative Example 1 A method for regenerating retired lithium iron phosphate (LFP) cathode materials specifically includes the following steps: (1) After the retired LFP battery was discharged and disassembled for 24 hours, the aluminum foil was separated by soaking in N-methylpyrrolidone (NMP). The resulting LFP cathode slurry was vacuum dried at 75°C for 10 hours to obtain the retired LFP cathode material (elemental composition: Fe 33.6wt%, P 18.5wt%, Li 3.8wt%, C 4.2wt%). (2) Place 100g of the retired LFP cathode material in a tube furnace, introduce CO2 gas with a purity ≥99.8 vol% until the partial pressure reaches 3.5 MPa, heat to 680°C at a heating rate of 5°C / min, keep warm for 5h to carry out the repair reaction, and after the reaction, control the temperature of the tube furnace to drop to room temperature at a cooling rate of 4°C / min, grind and pass through a 200-mesh sieve to obtain the intermediate material; (3) The intermediate material and 3g of lithium carbonate were mixed, anhydrous ethanol solvent was added, and the mixture was placed in a ball mill jar at a ball-to-material mass ratio of 10:1. The mixture was ball-milled at 400 rpm for 4 hours. The mixture was vacuum dried at 80°C for 12 hours, and then heated to 680°C at a heating rate of 5°C / min and kept at that temperature for 5 hours to carry out the calcination reaction to obtain the regenerated LFP cathode material. The carbon content was measured to be 3.3wt%.
[0039] Comparative Example 2 A method for regenerating retired lithium iron phosphate (LFP) cathode materials specifically includes the following steps: (1) After the retired LFP battery was discharged and disassembled for 24 hours, the aluminum foil was separated by soaking in N-methylpyrrolidone (NMP). The resulting LFP cathode slurry was vacuum dried at 75°C for 10 hours to obtain the retired LFP cathode material (elemental composition: Fe 33.6wt%, P 18.5wt%, Li 3.8wt%, C 4.2wt%). (2) Mix 100g of the retired LFP cathode material with 3g of lithium carbonate, add anhydrous ethanol, place in a ball mill jar at a ball-to-material mass ratio of 10:1, and ball mill at 400rpm for 4h. Dry the resulting slurry under vacuum at 80℃ for 12h to obtain a precursor mixture. (3) The precursor mixture was placed in a tube furnace and CO2 gas with a purity ≥99.8 vol% was introduced until the partial pressure reached 1.5 MPa. The mixture was heated to 680°C at a heating rate of 5°C / min and kept at the temperature for 5 hours for the repair reaction. After the reaction was completed, the temperature of the tube furnace was controlled to drop to room temperature at a cooling rate of 4°C / min to obtain the regenerated LFP cathode material. After grinding and passing through a 200-mesh sieve, the carbon content was measured to be 3.9 wt%.
[0040] Comparative Example 3 A method for regenerating retired lithium iron phosphate (LFP) cathode materials specifically includes the following steps: (1) After the retired LFP battery was discharged and disassembled for 24 hours, the aluminum foil was separated by soaking in N-methylpyrrolidone (NMP). The resulting LFP cathode slurry was vacuum dried at 75°C for 10 hours to obtain the retired LFP cathode material (elemental composition: Fe 33.6wt%, P 18.5wt%, Li 3.8wt%, C 4.2wt%). (2) Mix 100g of the retired LFP cathode material with 3g of lithium carbonate, 1.8g of β-cyclodextrin and 0.2g of catechol, add anhydrous ethanol, place in a ball mill jar at a ball-to-material mass ratio of 10:1, and ball mill at 400 rpm for 4 h. Dry the resulting slurry under vacuum at 80°C for 12 h to obtain a precursor mixture. (3) The precursor mixture was placed in a tube furnace and CO2 gas with a purity ≥99.8 vol% was introduced until the partial pressure reached 3.5 MPa. The mixture was heated to 680°C at a heating rate of 5°C / min and kept at the temperature for 5 hours for the repair reaction. After the reaction was completed, the temperature of the tube furnace was controlled to drop to room temperature at a cooling rate of 4°C / min to obtain the regenerated LFP cathode material. After grinding and passing through a 200-mesh sieve, the carbon content was measured to be 3.8 wt%.
[0041] The recycled LFP cathode material described in the examples and comparative examples was mixed with conductive carbon black and polyvinylidene fluoride at a mass ratio of 90:5:5 and coated onto an aluminum foil current collector to form a cathode sheet. Using lithium metal as the counter electrode and 1M LiPF6 / DMC:EC:EMC = 1:1:1 vol% as the electrolyte, CR2025 type button cells were assembled. Charge-discharge tests were conducted at a constant temperature of 25℃ to examine discharge performance, rate performance, and cycle performance. Specific test results are shown in Table 1 below. Table 1. Electrochemical performance of the recycled LFP cathode materials described in the examples and comparative examples.
[0042] As shown in the table above, the comparison between Example 1 and Comparative Example 1 indicates that the one-step integrated in-situ remediation method of "first replenishing lithium, then introducing CO2 for oxidation sintering" in Example 1 can effectively avoid the pollution problems and capacity loss risks that may be introduced during multi-step processing, resulting in the regenerated lithium iron phosphate (LFP) material exhibiting high discharge capacity and good cycle performance and rate performance. The comparison between Example 1 and Comparative Example 2 indicates that, under the same conditions, excessively low remediation pressure will adversely affect the electrochemical performance of the regenerated material. The comparison between Example 1 and Comparative Example 3 indicates that simply using β-cyclodextrin and catechol as additives has limited effect on improving the electrochemical performance of the regenerated lithium iron phosphate (LFP) material.
[0043] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A method for regenerating decommissioned lithium iron phosphate cathode materials, characterized in that, Includes the following steps: S1. Mix the retired lithium iron phosphate cathode material and lithium salt supplement in an organic solvent to obtain a precursor mixture; S2. The precursor mixture is subjected to a repair reaction under a high-pressure CO2 atmosphere to obtain recycled lithium iron phosphate material.
2. The method for regenerating decommissioned lithium iron phosphate cathode material according to claim 1, characterized in that, The retired lithium iron phosphate cathode material is obtained by discharging and disassembling retired lithium batteries, using N-methylpyrrolidone to dissolve the binder and electrolyte to separate the aluminum foil, and then drying the resulting slurry. Preferably, the discharge time is 24-48 hours; Preferably, the drying temperature is 70-80℃ and the drying time is 8-10h.
3. The method for regenerating decommissioned lithium iron phosphate cathode materials according to claim 1 or 2, characterized in that, In step S1, the lithium salt supplement is at least one of lithium carbonate, lithium hydroxide, lithium fluoride, lithium bromide, or lithium acetate; the organic solvent is a C1-C4 alcohol solvent, preferably ethanol. Preferably, the mass ratio of the decommissioned lithium iron phosphate cathode material to the lithium salt supplement is 100:0.5-5, and more preferably 100:2-3.
4. The method for regenerating decommissioned lithium iron phosphate cathode material according to any one of claims 1-3, characterized in that, Step S1 also includes the addition of catechol-modified cyclodextrin; Preferably, the mass ratio of the decommissioned lithium iron phosphate cathode material to catechol-modified cyclodextrin is 100:0.5-5, and more preferably 100:1-3.
5. The method for regenerating decommissioned lithium iron phosphate cathode material according to claim 4, characterized in that, The catechol-modified cyclodextrin is made by... β -The condensation of cyclodextrin with 1,3-propanediamine, followed by a Schiff base reaction with 3,4-dihydroxybenzaldehyde, yields the product. Preferably, the β The mass ratio of cyclodextrin, 1,3-propanediamine, and 3,4-dihydroxybenzaldehyde is 10:20-50:1-3.
6. The method for regenerating decommissioned lithium iron phosphate cathode material according to any one of claims 1-5, characterized in that, In step S1, the mixing method is ball milling. Preferably, the ball-to-material mass ratio of the ball mill mixture is 5-20:1, more preferably 8-12:1, and the rotation speed is 200-500 rpm, more preferably 300-400 rpm.
7. The method for regenerating decommissioned lithium iron phosphate cathode material according to any one of claims 1-6, characterized in that, In step S2, the partial pressure of the CO2 atmosphere is 2-5 MPa, preferably 3-3.5 MPa, and the purity of the atmosphere is ≥99.5 vol.
8. The method for regenerating decommissioned lithium iron phosphate cathode material according to any one of claims 1-7, characterized in that, In step S2, the temperature of the repair reaction is 500-800℃, preferably 670-690℃, the heating rate is 3-10℃ / min, and the time is 4-6h, preferably 4.5-5.5h. Preferably, the repair reaction further includes cooling to room temperature at a rate of 3-5°C / min.
9. A recycled lithium iron phosphate material, characterized in that, It is prepared by the regeneration method described in any one of claims 1-8.
10. A lithium-ion battery, characterized in that, It includes the recycled lithium iron phosphate material as described in claim 9.
Citation Information
Patent Citations
Methods for separating and repairing cathode materials from waste lithium iron phosphate batteries
CN106450558B
Methods for selective oxidation-reduction regeneration of spent lithium iron phosphate, and the regeneration of lithium iron phosphate and lithium-ion batteries.
CN113036253B
Modification method for directly repairing and regenerating lithium iron phosphate positive electrode material by pyrogenic process
CN114566727A
Direct repair method of highly-invalid positive electrode material in waste lithium ion battery
CN115000555A
